181 Computed Tomography Parameters for Atlanto-occipital Dislocation in Adult Patients: The Occipital Condyle-C1 Interval. (August 2015) - Martinez del Campo, Eduardo; Kalb, Samuel; Soriano Baron, Hector; Turner, Jay D.; Neal, Matthew; Uschold, Timothy David; Theodore, Nicholas
Abstract : INTRODUCTION: Our goal was to identify and compare the normal occipital-condyle-C1 interval (CCI) in healthy adults with the CCI in adults with atlanto-occipital dislocation (AOD) and establish a highly sensitive and specific cutoff value to diagnose AOD radiographically. METHODS: Eighty-one patients (59 non-AOD, 22 AOD) were included. Measurements obtained from thin-cut computed tomography scans of the craniovertebral joint to assess atlanto-occipital dislocation included: CCI, condylar sum, and standard diagnostic tools. RESULTS: Non-AOD patients were 50.8% (n = 30) male and 49.2% (n = 29) female, mean age was 42.4 ± 16 years (range 19-87 years). AOD patients were 45.5% (n = 10) male and 54.5% (n = 12) female with a mean age of 38.2 ± 9.7 years (range 20-56 years). Interrater reliabilities were all above 0.98 (95% CI) for CCI measurements. A total of 1296 measurements were made of the CCI in 81 patients. The mean CCI for non-AOD patients was 0.89 ± 0.12 mm, the single largest CCI measurement was 1.4 mm, and the largest mean for either right or left CCI was 1.2 mm. The mean condylar sum was 1.8 ± 0.2 mm, and the largest condylar sum value was 2.2 mm. Linear regression with age predicted an increase in CCI of 0.001 mm/y ( P < .05). The mean CCI in AOD patients was 3.35 ± 1.8 mm (range 1.5-6.4 mm). A cutoff value for AOD was determined at 1.5 mm for the CCI and 3.0 mm for the condylar sum, both with a sensitivity of 1 and false-negative rate of 0. Sensitivity for Powers, Wholey, Harris, Sun, Wackenheim, and Lee tests were determined to be 0.55, 0.46, 0.27, 0.23, 0.41, and 0.41, respectively. CONCLUSION: The revised CCI (1.5 mm) and condylar sum (3.0 mm) cutoff values have the highest sensitivity and specificity for the diagnosis of AOD in the adult population.